2021
DOI: 10.2334/josnusd.20-0082
|View full text |Cite
|
Sign up to set email alerts
|

Effect of food-simulating solvents on flexural properties of bulk-fill resin composites

Abstract: This study evaluated the flexural strength of bulk-fills after immersion in food-simulating solvents. Methods: Four overlapping segments along both sides of bar-shaped specimens (25 × 2 × 2 mm) made from bulk-fill composite were irradiated with an Elipar LED light-curing (1,200 mW/cm 2 for 20 s) device. The specimens were then divided into four groups (n = 20), according to storage media-namely, distilled water, 99% ethanol, heptane, and methyl ethyl ketone-at 37 o C for 4 weeks. Flexural testing was done with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…Despite the huge volume of gel holes remaining in the material, removing such macrodefects resulted in flex strengths of up to 70 MPa. [ 28 29 ] Some studies have shown a decrease of the flexural strength of composite resin when immersed in various fruit juices of different concentrations. [ 30 31 ]…”
Section: Discussionmentioning
confidence: 99%
“…Despite the huge volume of gel holes remaining in the material, removing such macrodefects resulted in flex strengths of up to 70 MPa. [ 28 29 ] Some studies have shown a decrease of the flexural strength of composite resin when immersed in various fruit juices of different concentrations. [ 30 31 ]…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Marghalani (2020), it has reported that the flexural strength post immersion in solvents such as distilled water, ethanol, and hexane shows no statistical significance ( P > 0.05), which is similar to our present study. [ 32 ]…”
Section: Discussionmentioning
confidence: 99%
“…Hybrid filler fractions and E-glass fibers (1–2 mm length), Ba-B-Si glass filler (0.1–2.2 µm) [ 17 ]…”
Section: Methodsmentioning
confidence: 99%